Effectiveness of ChatGPT vs. Perplexity AI in English Language Learning at the University of Serambi Mekkah - Sabrina, Sabrina; Shafa, Cut Firyal; Ainun, Ainun; Askia, Nur; Maisarah, Putri; Susilawati, Puja (LPPM STIKI Malang, 2024)
This study aims to compare the effectiveness of ChatGPT and Perplexity AI in the English Language Learning. It employs a mixed-method approach to determine the effectiveness of the two AI tools, ChatGPT and Perplexity AI, in improving English language learning at the University of Serambi Mekkah. Questionnaires and interviews were used to collect data. The results showed that 73.3% of participants favored the use of ChatGPT because of its interactive features and easy navigation. Sixty percent believed that ChatGPT provides more accurate information as opposed to Perplexity AI. This helps to motivate the learners and boost their confidence in using the language. Their counterpart, Perplexity AI, was preferred by a minority of respondents (13.3%) for its speed and accuracy. In this respect, ChatGPT was rated by participants as “highly effective” in improving their English skills, and 40% were “highly satisfied”. In contrast, only 26.7% considered Perplexity AI more effective and satisfying. Though ChatGPT is undeniably favored, the study acknowledges how Perplexity AI may serve as customized support, in satisfying specific needs regarding language learning. Both are very helpful for English language acquisition, though ChatGPT is favored because it is more appealing. These findings would be useful to educators in incorporating appropriate AI technologies into language curricula to meet various learners' needs and improve learning outcomes. This research has emphasized how AI tools support the more conventional ways of teaching a language and gives useful insight that is relevant to further education.